CIRCULATING CLONAL COMPLEXES AND SEQUENCE TYPES OF STREPTOCOCCUS PNEUMONIAE SEROTYPE 19A WORLDWIDE: THE IMPORTANCE OF MULTIDRUG RESISTANCE: A SYSTEMATIC LITERATURE REVIEW. (2nd January 2021) - Ruiz García, Yara; Nieto Guevara, Javier; Izurieta, Patricia; Vojtek, Ivo; Ortega-Barría, Eduardo; Guzman-Holst, Adriana
ABSTRACT: Introduction: Streptococcus pneumoniae is a major cause of morbidity and mortality, especially amongst young children and the elderly. Childhood implementation of pneumococcal conjugate vaccines (PCVs) significantly reduced the incidence of invasive pneumococcal disease (IPD), while several nonvaccine serotypes remained substantial. Although there is evidence of the impact of higher-valent PCVs on serotype 19A, 19A IPD burden and antibiotic resistance remain a major concern post-vaccination. Areas covered: We performed a systematic literature review to analyze the frequency and clonal distribution of serotype 19A isolates in the pre– and post-PCV era worldwide providing a scientific background on the factors that influence multidrug resistance in pneumococcal isolates. Expert commentary: Serotype 19A IPD incidence increased in all regions following the introduction of the 7-valent PCV. The higher-valent PCVs have reduced the rates of 19A IPD isolates, but several circulating strains with diverse antibiotic resistance prevailed. Heterogeneous clonal distribution in serotype 19A was observed within countries and regions, irrespective of higher-valent PCV used. An increase of 19A isolates from pre- to post-vaccination periods were associated with frequently occurring serotype switching events and with the prevalence of multidrug resistant strains. Rational antibiotic policies must be implemented to control the emergence of resistance. Plain Language Summary What is the context? Streptococcus pneumoniae is a major cause of pneumococcal diseases especially amongst young children and the elderly. Vaccination with pneumococcal conjugate vaccines has significantly reduced the incidence of invasive pneumococcal disease worldwide. However, the invasive pneumococcal disease remains an important health problem due to the increase of nonvaccine serotypes. Serotype 19A is predominant in many countries worldwide. Factors contributing to its prevalence include serotype replacement, the emergence of clones with multidrug resistance due to antibiotic overuse, and potential bacteria adaptation in response to the vaccine. What is new? We performed a systematic literature review to 1) analyze the incidence and clonal distribution of serotype 19A isolates pre- and post-vaccination worldwide, and to collect data evaluating antimicrobial resistance patterns displayed by the clones of serotype 19A. We found that 1) clonal distribution in serotype 19A was heterogeneous within countries and regions, irrespective of the vaccine used; 2) the diversity of 19A isolates increased after vaccination. It was associated with frequent serotype switching events and with the prevalence of multidrug resistant strains. What is the impact? Implementation of policies to educate on sustainable antibiotic use and infectious prevention measures may help control the emergence of antibiotic resistance. High-quality active surveillance and future molecular epidemiology studies are needed to understand rapid genetic changes.